CircFAM114A2 Promotes Cisplatin Sensitivity via miR-222-3p/P27 and miR-146a-5p/P21 Cascades in Urothelial Carcinoma - Lv, Jiancheng; Zhou, Zijian; Wang, Jingzi; Yang, Xiao; Yu, Hao; Han, Jie; Feng, Dexiang; Yuan, Baorui; Wu, Qikai; Li, Pengchao; Lu, Qiang; Yang, Haiwei (Frontiers in oncology, 2021)
Circular RNAs (circRNAs) are non-coding RNAs that have the structure of a covalently closed loop. Increasing data have proven that circRNAs can influence the progression and chemotherapy sensitivity of tumors. Therefore, the underlying function and mechanisms of more circRNAs in progression and chemotherapy resistance are important. We conducted RNA sequencing on five pairs of urothelial carcinoma samples and screened for circRNAs. CircFAM114A2 was found to be low expressed in urothelial carcinoma. The functions of circFAM114A2 in urothelial carcinoma were explored by cell cycle assay, IC determination assay, cell proliferation assay, apoptosis assay, and tumorigenesis assay. We discovered that the levels of circFAM114A2 were decreased in urothelial carcinoma cell lines and tissues. According to follow-up data, urothelial carcinoma patients with higher circFAM114A2 expression had better survival. Importantly, the levels of circFAM114A2 were associated with the histological grade of urothelial carcinoma. CircFAM114A2 could inhibit cell proliferation and block more urothelial carcinoma cells in the G1 phase and then increase the sensitivity of urothelial carcinoma to cisplatin chemotherapy. Mechanistically, circFAM114A2 directly sponged miR-222-3p/miR-146a-5p and subsequently influenced the expressions of the downstream target genes / , which, in turn, inhibited the progression of urothelial carcinoma and increased the sensitivity of cancer cells to cisplatin chemotherapy. CircFAM114A2 could inhibit progression and promote cisplatin sensitivity in urothelial carcinoma through novel circFAM114A2/miR-222-3p/P27 and circFAM114A2/miR-146a-5p/P21 pathways. CircFAM1142 has therefore great potential as a prognostic biomarker and therapeutic target for urothelial carcinoma.